EFEKTIVITAS KKG AGAMA HINDU MELALUI PRAKTEK DAN SISTEM UMPAN BALIK DALAM MENINGKATKAN KOMPETENSI GURU MENYUSUN RPP INOVATIF BERKARAKTER - I Ketut Kalpadiana (Pascasarjana Universitas Hindu Indonesia, 2015)
The training strategy with the feed-back technique was designed to be applied in three cycles. Theresult of the KKG activity through the training with feed-back technique has been proven to have effect in increasing the commitment of the Hinduism teachers within the elementary schools included in cluster 1 in Blahbatuh district around the school year of 2012/2013 in completing the Learning Plan (RPP) with innovative and characterized ideals. The work indicators: at least 90% of the number of the teachers has indicated the good commitment in deciding the assessment instrument (the mean value of 4,00-5,00) within the scale of 1-5 which was achieved during the cycle 3 with the accomplishment of 100%. Besides, the teacher competence in deciding the assessment instrument that conformed to the 2013 curriculum reached 100% as well.